Mechanical production and stabilisation of submicron particles in stirred ball media mills - Peukert, Wolfgang; Mende, Stefan; Stenger, Frank; Schwedes, Jörg (Powder Technology, 2003)
A joint research project between the Technical University of Braunschweig and the Technical University of München investigates the possibilities for the production of stable product suspensions in a particle size range smaller than 100 nm. This paper shows the experimental setup which allows the measurement of the most important electrochemical properties and the analysis of the particle size distribution of the product suspension as well as an adjustment of the pH value for stabilization during the comminution process. Results for comminution of fused corundum with different grinding media materials and grinding media sizes are shown. In addition, results showing the influence of the electrostatic stabilization on the grinding progress are presented. Further, the rheology of the product suspension is examined depending on grinding progress and suspension stabilit
UnivIS-Import:2015-03-09:Pub.2003.tech.ITC.mechve.mechan
Keywords: Ultrafine grinding; Submicron particles; Stirred media mill; ζ potential; Electrostatic stabilization; Fused corundum